Labor Trafficking in Missouri: Revelations from a statewide needs assessment. Issue 1 (2nd January 2023) - Preble, Kathleen; Nichols, Andrea; Cox, Ashley
ABSTRACT: Knowledge about labor trafficking (LT) lags behind extant understanding about sex trafficking due to the ability of LT to exist within legal frameworks, and it impacts some of the most oppressed and marginalized groups of people within our society. While the anti-trafficking movement is developing better understanding about LT broadly, nuances around the regions and industries in which LT exists, and the unique needs experienced by survivors have yet to be fully explored. Through an electronic survey a statewide needs assessment and count study was conducted. Of the 107 total service provider respondents, three indicated having worked only with LT survivors and 13 providers indicated they served survivors with both labor and sex trafficking experiences. These 16 providers indicated they had served 20 labor trafficking only and 53 labor/sex trafficking survivors in the prior 12 calendar months. Respondents provided unique insight about the types of LT victimization survivors had experienced in this small mid-western state as well as unique needs among this population. Implications of these insights are discussed within the context of service provision and policy.